KESATUAN SURAT AL-QUR’AN DALAM PANDANGAN SALWA M.S. EL-AWWA - Adrika Fithrotul Aini (SYAHADAH : Jurnal Ilmu al-Qur'an dan Keislaman, 2015)
Munasabah is one  of  the  Quranic  sciences  which  undergoes development.  Thus,  this article  will  discuss  this  munasabah,  or integral surah in the Qur-an based on Salwa el-Awwa’s approach. It explains the theory by using the descriptive method. It resultsthat  the  new  concept  offered  by  Salwa  concerning  Quranic Munasabah explains  her  curiosity  toward  developing  integrated surah in the Quran. This concept is aimed at dividing the themes of thesurah objectively and not intuively. So, the theory in orderingunity  of  Quranic  surah  is  based  on  coherence  and  relevanceby using pragmatic approach.Keywords: Munasabah, Coh